EFFECT OF TRANSPLANTATION OF PANCREAS CELL CULTURE IN ALLOXAN DIABETES MELLITUS IN RATS IN AN EXPERIMENTAL (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
Despite the significant advances achieved in modern diabetology, a number of questions remain open, which requires further study of this pathology and improvement of ways to correct it. Experimental diabetology is of great importance for identifying issues of pathogenesis, clinical picture, treatment and prevention of the disease. Experimental models of diabetes mellitus provide valuable information not only for understanding the pathophysiology of the disease, but also the mechanism of the antidiabetic action of various drugs for the purpose of their targeted use [1, 2, 4]. The alloxan model of diabetes mellitus in animals is optimal at the current level of development of experimental diabetology, because fully corresponds to the pathogenesis of diabetes mellitus in humans [2, 3, 5].